3D game development for cobot-human interaction using unity - Wang, Fanxu (Nanyang Technological University, 2022)
With the recent release of the metaverse concept, 3D game development together with VR/AR physical headsets has become more and more important in our human society. Game development no longer only focuses on video games, but really contributes to manufacturing, human society, and eventually building a virtual world focused on human connection.